Determination of fitness traits of Orius strigicollis Poppius (Hemiptera: Anthocoridae) on Pectinophora gossypiella (Lepidoptera: Gelechiidae) using two-sex life table analysis - Shahzaib Ali; Qian Zhu; Waqar Jaleel; Shakeel Ur Rehman; Muhammad Asim Rasheed; Muhammad Musa Khan; Yasir Islam; Muhammad Hafeez; Xingmiao Zhou (PeerJ, 2020)
Background Pink bollworm (Pectinophora gossypiella) is a destructive insect pest of cotton crops in China and globally, which is actively predated on by Orius strigicollis. Studies on the fitness or survival of O. strigicollis fed on P. gossypiella at different temperatures have not been reported. The fitness of O. strigicollis may be well explained using two-sex life table parameters. Thus, the present study provides important insights for the effective biocontrol of P. gossypiella. Methodology Considering the importance of fitness parameters and biocontrol, the present study explores the feeding potential and age-stage, two-sex life table traits of O. strigicollis on P. gossypiella eggs at different temperatures (24, 28 and 32 °C) in the laboratory. Results The intrinsic rate of increase (r) was higher at 28 °C (0.14 d−1) than at 24 °C (0.0052 d−1) and 32 °C (0.12 d−1). Similarly, the net reproductive rate (R0) was higher at 28 °C (17.63 offspring) than at 24 °C (1.13 offspring) and 32 °C (10.23 offspring). This concluded that the maximum feeding potential and growth capacity of O. strigicollis could be attained at 28 °C when fed on P. gossypiella eggs. O. strigicollis adults preferred to feed on P. gossypiella eggs compared with first instar larvae. Based on these results, the present study suggests that O. strigicollis represents a promising biological control agent against P. gossypiella eggs in cotton fields.